Optimizing film and television advertising placement strategies in the digital media ecosystem: a study based on a three-party stochastic evolutionary game - Zhang, Lu (Frontiers in Communication, 2025)
With the acceleration of digitalization, digital media and streaming platforms have driven the rapid development of advertising placement business models in the film and television industry. Producers increasingly depend on advertising revenue, advertisers prioritize return on investment, and viewers’ grow more resistant to advertising interruptions, intensifying the tension among stakeholders. Most existing studies focus on bilateral relationships and neglect the strategic behavior of viewers, which limits their ability to explain persistent cooperation failures in real-world advertising ecosystems. To address this, this study develops a three-party stochastic evolutionary game model involving film producers, advertisers, and viewers, incorporating key variables such as advertising dissemination effectiveness, content quality, and advertising costs to simulate strategy evolution under uncertainty. Simulation results indicate that improving content quality from 100 to 200 increases viewers’ ad acceptance from 0.32 to 0.84 and raises producer cooperation willingness by more than 70 percent. In contrast, when embedded advertising costs rise from 100,000 to 500,000 RMB, cooperation willingness among both producers and advertisers drops below 0.1. While increased returns from inserted ads may briefly raise producer engagement, they have minimal effect on viewers’ acceptance and tend to destabilize the system. This study identifies a structural mismatch in stakeholder incentives and introduces a dynamic modeling approach that captures nonlinear interactions and adaptive behavior using continuous strategies and stochastic disturbances. The findings suggest that technical improvements or revenue redistribution alone are insufficient to ensure sustainable cooperation. Enhancing content quality is the only effective lever for aligning stakeholder interests, breaking low-cooperation equilibria, and promoting long-term system stability, offering both theoretical contributions and practical guidance for platform governance and advertising strategy design.